MATHEMATICAL FALLACY PESERTA OLIMPIADE SAINS NASIONAL MATEMATIKA DALAM ALJABAR - Sukardi, Sukardi; Mirza, Ade; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research is to describe the form of mathematical fallacy and its causing factors. The research method used is descriptive method in the form of case study research. The subjects of this research are eight senior high students, four students from SMAN 1, two students from SMA Santo Paulus and two students from SMAN 3, who participated in National Science Olympiad 2019 in Pontianak. Mathematical fallacy in this research consists of three forms. They are division by zero, mistaken of taking squares and exponent fallacy. Mathematical fallacy in the form of division by zero was done by 5 students, mistaken of taking squares was done by 6 students, while exponent fallacy was done by 8 students. It was concluded that there were five factors leading to mathematical fallacy. Those are (1) Students were trying to skip several mathematical procedures who claimed as not substantive; (2) Students lacked of understanding in using the argumentation scheme in the form of procedural/steps to solve the problems; (3) Students took the conclusion hastily without depth analysis; (4) Teachers tend to skip certain facts, concepts, principles and mathematical procedures; and (5) Some text books students used contain things which may lead to mathematical fallacy.Keywords: Mathematical Fallacy, Olympiad, Procedure